Thermosetting CFRP interlaminar toughening with multi-layers graphene and MWCNTs under mode I fracture. (20th October 2019) - Liu, Bin; Cao, Shuanghui; Gao, Nongyue; Cheng, Laifei; Liu, Yongsheng; Zhang, Yi; Feng, Dan
Abstract: Unidirectional carbon fiber-reinforced composites are widely applied in aeronautical and astronautical structures. However, the weak interlaminar toughness makes composite structures easily being damaged under the low energy impact. Improving composite interlaminar toughness without increasing thickness becomes possible as the carbon nanotubes(CNTs) and graphene possess superstrong-mechanical property and nanoscale. This paper focuses on enhancing the mode I fracture toughness by adding two nano materials of multi-walled carbon nanotubes(MWCNTs) and multi-layers graphene(mG) into interlaminar surface. MWCNTs and mG are sprayed on the central two plies interlaminar surface at the same density 1 g/m 2 . Double cantilever beam(DCB) standard test is used to investigate the mode I energy release rate with different toughening strategies. Increasing proportion of the mean fracture toughness of crack propagation are 12.3% (MWCNTs) and 101.4% (mG) respectively. According to SEM analysis, the horizontal multi-layers graphene surface peeling and the vertical pull out mechanisms improve the crack growing resistance and result in large amount of fiber breakage and bridging. It is also revealed that the multi-layers graphene relatively-larger surface area compared with MWCNTs makes the interlaminar fracture toughness increasing notably. Based on finite element method(FEM) of continuum damage mechanics, the original and mG toughened specimen under DCB mode I fracture are modeled and analyzed. The simulation and experiment are in good agreement.